2010
DOI: 10.2174/156800910793605839
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant CXCR4 and CXCR7 Expression Predicts Poor Prognosis in Renal Cancer

Abstract: CXCR4 is a chemokine receptor implicated in the metastatic process. The CXCR4 ligand, CXCL12, was shown to bind also the CXCR7 receptor, a recently deorphanized chemokine receptor whose signalling pathway and function are still controversial. This study was conducted to determine patients clinic-pathological factors and outcome according to the expressions of CXCR4 and CXCR7 in renal cell carcinoma (RCC). CXCR4 and CXCR7 expression was evaluated in 223 RCC patients through immunohistochemistry; moreover CXCR4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 0 publications
6
52
0
Order By: Relevance
“…Meta-influence analysis did not suggest undue influence of any single study. Although five studies appeared to be outliers [8, 25, 63, 66, 77], we did not find clinical heterogeneity justifying their exclusion. Subsidiary analyses were carried out in the analysis of PFS (Figure 2B).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Meta-influence analysis did not suggest undue influence of any single study. Although five studies appeared to be outliers [8, 25, 63, 66, 77], we did not find clinical heterogeneity justifying their exclusion. Subsidiary analyses were carried out in the analysis of PFS (Figure 2B).…”
Section: Resultsmentioning
confidence: 55%
“…Forty-seven studies, with a total of 5,592 patients, included data on progress free survival in 12 types of cancer 8, 10, 12, 14-27, 31-33, 35, 38-40, 43, 45-48, 53, 56, 63-66, 70, 73, 75, 77-80, 82, 83, 85, 88, 89]. Of all the participants, 2583 (46%) were CXCR4 over-expression.…”
Section: Resultsmentioning
confidence: 99%
“…Also, in patients with known metastatic RCC, CXCR4 was shown to be expressed on circulating pan-cytokeratin-positive RCC cells (Reckamp et al, 2009). Several studies in preclinical models also confirmed that the CXCR4/CXCL12 axis regulates invasiveness, angiogenesis, and organ-specific metastasis of RCC (D’Alterio et al, 2010; Gahan et al, 2012; Wang et al, 2012, 2009). CXCR4 expression in RCC is correlated with metastatic potential in orthotopic mouse models of human RCC xenografts (Pan et al, 2006).…”
Section: Role Of Cxcr4 In Cancermentioning
confidence: 75%
“…CXCR4 and CXCR7 expression levels were also linked to early and metastatic recurrence in non-small cell lung cancer (63). High CXCR7 expression was inversely correlated with 5-year disease-free survival of patients with non-small cell lung cancer and renal cancer (63,64). Interestingly, targeted overexpression of CXCL11/ITAC in tumor sites displayed antitumor activity in a murine cancer model, and ITAC also served as a potent antagonist of transendothelial migration of CXCR4-and CXCR7-positive human tumor cells (25,65).…”
Section: Discussionmentioning
confidence: 99%